2011
DOI: 10.1603/ec10200
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ozone Fumigation Against the Major Grain Pests in Stored Wheat

Abstract: Field experiments were conducted in steel bins containing 13,600 kg of hard red winter wheat, Triiticum aestivum L. One bin was treated with ozone and the second bin served as a control. Stored grain insects were placed in bins for 1-, 2-, 3-, and 4-d exposure periods in sampling tubes to test ozone concentrations of 0, 25, 50, and 70 parts per million by volume (ppmv). Ozone treatments on eggs and larvae of Plodia interpunctella (Hübner) were not effective, but pupae were more susceptible. Sitophilus oryzae (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 14 publications
1
45
1
Order By: Relevance
“…Also, Isikber and Oztekin (2009) found that pupae of T. confusum were more resistant to ozone than larvae. In contrast to the present results, Bonjour et al (2011) evaluating the efficacy of ozone fumigation against the major grain pests in stored wheat, reported that pupae of P. interpunctella were more susceptible than eggs and larvae.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Also, Isikber and Oztekin (2009) found that pupae of T. confusum were more resistant to ozone than larvae. In contrast to the present results, Bonjour et al (2011) evaluating the efficacy of ozone fumigation against the major grain pests in stored wheat, reported that pupae of P. interpunctella were more susceptible than eggs and larvae.…”
Section: Discussioncontrasting
confidence: 99%
“…Niakousari et al (2010) reported that a concentration of 4.000 ppm of ozone for 2 h resulted in only 80% mortality of P. interpunctella eggs on date fruits. Bonjour et al (2011) found that ozone at a concentration of 70 ppm for a period of 4 days did not have a significant effect on the eggs of P. interpunctella. These results show that eggs are more resistant to ozone.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, 100% mortality of Sitophilus oryzae and T. castaneum adults was observed after 2 and 4 d, respectively, following the application of 50 or 70 ppm ozone gas in wheat (BONJOUR et al, 2011); and 100% mortality of S. zeamais and T. castaneum adults and a 96% reduction of Aspergillus flavus was observed following the addition of ozone gas at 258,120 ppm/min in corn kernels (MCDONOUGH et al, 2011a). Full mortality of T. castaneum pupae and eggs and P. interpunctella eggs required a treatment of 180 min, and S. zeamais and S. oryzae, respectively, required 120 and 60 min at 1800 ppm ozone (MCDONOUGH et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…In field trials, Kells et al (2001) used a CTP of at least 3,600 ppm-h and consistently achieved 92% to 100% mortality for adult MW and adult RFB in their studies. In field trials, Bonjour et al (2008Bonjour et al ( , 2011 observed 100% mortality of adult RFB with a CTP of 4,800 ppm-h and of adult rice weevil (RW) with 2,400 ppm-h. Based on the limited literature available, it appears that the CTP for effective insect control varies by species and life stages, and requires further investigation. However, based on these laboratory experiments and field trials, it can be assumed that aiming for a CTP of at least 3,600 ppm-h should result in 90% to 100% mortality of adult-stored product insects.…”
mentioning
confidence: 99%